Konsep dan Hirarkhi Teungku di Aceh - Nirzalin, Nirzalin (Universitas Malikussaleh, 2013)
This study examines the concept and hierarchy of teungku in Aceh. The main question to answer in this research is what is the main concept of teungkuÂ in Aceh And then how the hierarchy of teungku in Acehnese society.This research took placed in north Aceh district.Theoretical perspective adopted in this research was Geertzâs meaning of religion. And ethnographic collection method was utilized through involved observations, in-depth interviews, and also documentation study. This study found that status of teungku in Acehnese society is open or achieved status. Itâs meanÂ everyone in different social background and strata got this status if he has capacity. The capacity needed in this status are broadly Islamic knowledge and highly spirituality. The measured of that capacity depend on evaluation of society.Teungku in Aceh divided to five categories i.e teungku dayah, teungku balee, teungku rangkang, teungku meunasah and pak teungku. That categories depend on their charisma and roled in society. That categories also showed different charisma amoung them. In fact, teungku is the main actor who determinant all of behaviors and actions of Acehnese society inÂ social, political and cultural fields mainly for villagers.